Identification of resistance source for gall fly, Asphondylia sesami Felt (Diptera: Cecidomyiidae) in sesame: Identification of resistance source for gall fly, Asphondylia sesami Felt (Diptera: Cecidomyiidae) in sesame - T BOOPATHI,; K T RAMYA,; A L RATHNAKUMAR,; P DURAIMURUGAN, (Journal of Oilseeds Research, 2023)
The incidence of the gall fly (Asphondylia sesami Felt) was found during flowering period of sesame. The sesame genotypes (n=61) were screened for A. sesami and incidence of A. sesami varied from 0 to 15.77%. Two genotypes viz., ISWG-20-05 and IIOS-1103 were found free from A. sesami incidence. The highest A. sesami incidence was noted in GT 10 (10.12%) and RJR 170 (15.77%).